Preparing of the Future Pedagogue to Realization of Person-Centered Learning - Lyudmyla Mashkina (Pedagogical Discourse, 2013)
In the article the features of training of the future teachers to implement learner-oriented learning are revealed. The main components of the readiness of students for such training: motivational, informative, methodical are determined. Motivational component, in particular, provides for the formation of the motives and goals of personality oriented pedagogy; substantial - a system aimed at the acquisition of knowledge of personality-oriented training courses teaching methods and subject-cycles, and the methodological component aims at technological skills in the context of the above teaching. Pedagogical conditions of effective preparation of the future teachers to personally oriented learning are elucidated.